Product lifecycle management in the digital twin era : 16th IFIP WG 5.1 international conference, PLM 2019, Moscow, Russia, July 8-12, 2019, revised selected papers /: 16th IFIP WG 5.1 international conference, PLM 2019, Moscow, Russia, July 8-12, 2019, revised selected papers. ([2019]) - Unknown
No abstract available